The Nexus of Crowdfunding and e-Wakaf to Islamic Fintech in Indonesia in the Era of Industrial Revolution 5.0 - WAHYUDI, HERU; TUBARAT, CHARA PRATAMI TIDESPANIA; RODLIYAH, NUNUNG; KUSNADI, ANDI; LENY, SANDRA MEI (Journal of Ecohumanism, 2024)
This study analyses the contribution of digitalisation in Islamic finance through the application of Islamic crowdfunding and e-wakaf instruments in supporting the development of Islamic fintech in Indonesia, especially in the era of the Industrial Revolution 5.0. Digitalisation in the Islamic finance sector plays a strategic role in expanding access to financial inclusion and facilitating more effective community involvement in sharia-based economic activities. Using the Robust Least Squares (RLS) method, this study utilises secondary data for the period 2018 to 2023 to evaluate the impact of Islamic crowdfunding and e-wakaf on the growth of Islamic fintech. The results show that Islamic crowdfunding significantly expands access to alternative funding, especially for small and medium enterprises (SMEs), while e-wakaf improves transparency and efficiency of waqf asset management through digital technology. These two instruments simultaneously contribute positively to the strengthening of the Islamic fintech ecosystem in Indonesia, creating a strong foundation for broader and sustainable financial inclusion. The findings provide important perspectives for the development of innovative policies and strategies in advancing the Islamic financial sector in the digital era.